2006
DOI: 10.1007/s11082-006-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Waveguide Grating for Normal TM Mode Coupling

Abstract: The conditions for maximum longitudinal electric field of a TM mode at the surface of a step index slab waveguide, and the value of this maximum are given in a normalized analytical form. They are applied to a grating coupling structure corresponding to a resonant laser mirror or to optical interconnects involving a normally incident free space wave and a singlemode slab waveguide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The silicon nitride layer of deposited thickness t = 0.27Λ, is etched on a depth h = 0.15Λ. These parameters may be further optimized but are already suitable for good sensitivity [ 13 ]. To span around the resonance, we vary the filling factor of micropads f m = d m /Λ, with d m the groove width (1 ≤ m ≤ M) while other parameters (period Λ, waveguide layer thickness t, etching depth h) are kept constant.…”
Section: Model Of Stepped Duty-cycle Peak Tracking Resonance Detecmentioning
confidence: 99%
“…The silicon nitride layer of deposited thickness t = 0.27Λ, is etched on a depth h = 0.15Λ. These parameters may be further optimized but are already suitable for good sensitivity [ 13 ]. To span around the resonance, we vary the filling factor of micropads f m = d m /Λ, with d m the groove width (1 ≤ m ≤ M) while other parameters (period Λ, waveguide layer thickness t, etching depth h) are kept constant.…”
Section: Model Of Stepped Duty-cycle Peak Tracking Resonance Detecmentioning
confidence: 99%
“…On the other hand, the fabrication of quasi-2D planar PhC structure considered in the grated waveguide (GWg) systems is more amenable to the existing fabrication technology [16]. As a result, more reliable experimental verification of the numerical models can be performed on these systems as reported in [16][17][18][19][20]. This type of structures, while relatively simplified, still offer a large enough room for the exploration of a wide ranging applications with enhanced and new functionalities [19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of planar GWg systems and their promising applications have been reported previously by a number of research groups [17][18][19][20][21][22], and different numerical tools have been developed by different research groups such as the method of lines, finite difference time domain, eigenmode expansion, etc. [8,23].…”
Section: Introductionmentioning
confidence: 99%